Evidence of Cheshmeh Ali Culture in Chenaran Plain (Northeastern Iran) (Global Journal of Human-Social Science, 2014)
Despite the strategic position and specific economic conditions of Khorasan Province including location in the course of the route linking East to West and distinctive mineral resources, no integrated study has been conducted to date for understanding the prehistoric cultures in this province. Therefore, archaeological excavations in Chenaran site as a major site in Mashhad Plain can elucidate the dark archeological aspects and chronological vacuum in this field. Chenaran site is located on the northern margin of the current city of Chenaran in Khorasan Razavi Province. It was excavated in the summer of 2012. The main objectives were to estimate the extent of the prehistoric site of Chenaran and present relative and absolute chronology from the lower layers to the end of settlement, and fortunately considerable results in this field were achieved. In this paper, only the relative chronology results have been pointed, and it is hoped that absolute chronology results are independently released in another article, which is currently under consideration. According to the pilot study and in a comparative approach with the settlements in southwestern Turkmenistan, Chenaran site pottery is comparable with Anu Ia to Namazgah III period.
Keywords: chenaran site; cheshmeali culture; anu culture; namazgah culture